International Efforts to Combat Corruption and States’ Concern; a Perspective toward Indonesia-Singapore Extradition Treaty after 4.5 Years of Silence - Iqbal, M. Putra (UI Scholars Hub, 2012)
The United Nation Convention against Transnational Organized Crime (UNTOC) and the United Nations Convention against Corruption (UNCAC) is a symbol of international community efforts in combating corruption. Most states are state parties to both convention including Indonesia and Singapore. However, domestic politics such as ratify cation by parliament has influenced states’ commitment in combating corruption. Indonesia-Singapore Extradition Treaty was signed in 2007. However, it has not entered into force yet and this is a good example on domestic politics that influences states’ policy and even states’ commitment on an international issue. This extradition treaty therefore, has no strong legal power toward both states since both states just expressed consent to be bound and subject to ratify cation. However, both states should show good faith in continuing the treaty and become legally binding.